Driving Under the Influence of Drugs: A Single Parallel Monitoring-Based Quantification Approach on Whole Blood - Joye, Timothée; Rocher, Katell; Déglon, Julien; Sidibé, Jonathan; Favrat, Bernard; Augsburger, Marc; Thomas, Aurélien (Frontiers in Chemistry, 2020)
Driving under the influence of psychoactive substances is an important cause of motor vehicles crashes. The identification and quantification of substances most frequently involved in impaired-driving cases in a single analytic procedure could be an important asset in forensic toxicology. In this study, a highly sensitive and selective liquid chromatography (LC) approach hyphenated with Orbitrap high-resolution mass spectrometry (HRMS) was developed for the quantification of the main drugs present in the context of driving under the influence of drugs (DUID) using 100 µL of whole blood. This procedure involves a simple sample preparation and benefit from the selectivity brought by parallel reaction monitoring (PRM) allowing to solve most DUID cases using a single multi-analyte injection. The method was fully validated for the quantification of the major classes of psychoactive substances associated with impaired-driving (cannabinoids, cocaine and its metabolites, amphetamines, opiates and opioids and the major benzodiazepines and z-drugs). The validation guidelines set by the “Société Française des Sciences et des Techniques Pharmaceutiques » (SFSTP) were respected for 22 psychoactive substances using 15 internal standards. Trueness was measured to be between 95.3 and 107.6 % for all the tested concentrations. Precision represented by repeatability and intermediate precision was lower than 12 % while recovery (RE) and matrix effect (ME) ranged from 49 to 105 % and from -51 to 3 % respectively. The validated procedure provides an efficient approach for the simultaneous and simple quantification of the major drugs associated with impaired driving benefiting from the selectivity of PRM.